The Folate Concentration and/or Folic Acid Metabolites in Plasma as Factor for COVID-19 Infection - Acosta-Elias, Jesus; Espinosa-Tanguma, Ricardo (Frontiers in Pharmacology, 2020)
Pregnant women appear to be more susceptible to infectious diseases than women in reproductive age. According to the California Department of Public Health pregnant women were 9.6 folds more likely to be hospitalized during the 2009 influenza outbreak when compared to non-pregnant women in reproductive age. In contrast, it was reported that of 16,749 COVID-19 patients that were hospitalized in the UK, the probability for pregnant women to require in-patient care due to infection by SARS-CoV-2 was 0.95 versus non-pregnant women. Therefore 9.6/0.95= 10.10, which brings us to the conclusion that pregnant women are 10.10 folds less likely to be hospitalized for a SARS-CoV-2 infection than for the 2009 H1N1 pandemic. Folic acid supplementation during pregnancy could be the factor that is protecting these patients against SARS-CoV-2 infection. Two independent papers that used informatic simulation proved that folic acid reduced the replication of this virus. One of them showed that folic acid inhibits the furin protease which the virus needs in order to enter its host cell, while the other one explained that folic acid inactivates protease 3CL$^{pro}$, a protein that the virus needs to replicate. Nonetheless the probability that folic acid blocks two different proteins is very low, therefore the mechanism by which folic acid has apparently protected pregnant women during the COVID-19 pandemic has not been determined.